PENENTUAN DOSIS KAPORIT SEBAGAI DESINFEKTAN DALAM MENYISIHKAN KONSENTRASI AMMONIUM PADA AIR KOLAM RENANG - Dheasy Herawati; Anton Yuntarso (Faculty of Health Sciences Universitas Maarif Hasyim Latif, 2017)
Disinfectant commonly used in water swimming pools is calcium hypochlorite Ca(OCl) 2 . Calcium hypochlorite is disinfectant which is used in the cleaning of water due to a searchable, inexpensive and contain approximately 70% chlorine. The use of calcium hypochlorite with improper doses will cause the formation of trihalomethane (THMs) compounds which are toxic and carcinogenic nature so that the use of calcium hypochlorite should be based on the calculation of Break Point Clorination (BPC) in order to secure for the environment. The purpose of the research was determine the opyimum dose of calcium hypochlorite in the form of crystal and solution for removal concentration of ammonium. The results obtained from the research that the optimum dose in the water swimming pools for disinfection process is not more than 10 g/L. The addition of calcium hypochlorite in the form of crystals can be removal the concentration of ammonium of 87.50% and in the form of aqueous solution of 83.30%. so it can be deduced that the addition of calcium hypochlorite in the form of crystals better than as a solution to removal the concentration of ammonium.